Functionality, safety and usability of a digital platform supporting executive functions in children with specific educational support needs - Costescu, C.; Ferreira, P.; Ferreira, A.; David, C.; Herrera, G.; Heldal, I.; Dæhlen, A.; Kovari, A.; Brito, J.; Campos, J.; Vera, L.; Stilwell, D.; et al. (Journal of Enabling Technologies, 2026)
Purpose This study examines the usability, acceptability and technical implementation of an adaptive digital platform that supports executive functions and emotion regulation in children with specific educational support needs (SESN), aiming to facilitate their personal, social, and academic growth. Design/methodology/approach A process of co-design was followed for the definition of the functionality of the digital platform, including the participation of focus groups of teachers working with children with SESN and the participation of independent panels of neurodivergent adults. The digital platform for assessing and training executive functions has been developed, integrating gamification, artificial intelligence and sensory technologies (eye-tracking and wearables). A total of 27 children with SESN aged 8–14 years participated in the pilot study. Findings Results suggest that +85% of children mention appropriate game time and ease of navigation. Approximately half of the teachers (48%) report that the game settings are excellent to very good. These contributions provide guidelines for IT technicians and constitute standards of use for teachers and children with NDDs. This study has demonstrated the functionality, safety and usability of the developed digital platform. It also helped in the identification of opportunities for improvement in the design and implementation of that platform, pushing it forward for subsequent experimental validation. Originality/value Previous studies investigated the effectiveness of separate cognitive tasks for training executive functions with children with SESN. However, no study has been conducted to validate a digital platform as a unitary assessment battery for these functions and its feasibility to be used in a school setting. This digital platform is also the first one to integrate gamification, artificial intelligence and sensory technologies for assessing and training executive functions in children with SESN.